Double Pseudonym-Based Privacy Preservation Scheme for securing sensitive information in the SaaS cloud environment - et.al, V.Ganesan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the modern world, cloud computing is considered as the essential entity of diversified number of organization for assisting them towards the utilization of demand resources. In this context, cloud providers need to adhere to the privacy and security mechanisms in order to attain confident and secure exchange of user sensitive data in cloud environment. Thus, the data exchanged by the users in the cloud scenario need to be secured enough to resists the possible kinds of attacks that could be launched by the attackers. In this paper, Double Pseudonym-Based Privacy Preservation Scheme (DPBPPS) is proposed for securing sensitive data shared on the cloud. This DPBPPS includes a significant authentication scheme that inherited the benefits of the double pseudonym method for preventing the real identity of the cloud users by periodically updating the information (such as member secret, authentication key, internal pseudo-identity). This DPBPPS prevents the inclusion of bilinear pairing for yielding better performance in terms of computation overhead and communication overhead, and is more suitable to be applied independent to the number of users and sensitive data shared over the clouds.